Building a Basic Mathematics Foundation Through Deep Learning Policies for Grades 4-6 Elementary School Students - Firmansyah Firmansyah; Husnia Husnia (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze how deep learning policies can play a role in building basic mathematical foundations in elementary school students, particularly those in grades 4–6. The background of this study is based on the low numeracy skills of Indonesian students as shown by the results of PISA 2022 and the National Assessment. To address this issue, this study uses the Systematic Literature Review (SLR) method by reviewing scientific articles published between 2020 and 2025 from various academic sources such as Google Scholar and Scopus. The results of the study show that the implementation of deep learning at the elementary school level is effective in improving conceptual understanding, critical thinking skills, and motivation to learn mathematics. Approximately 60% of the studies highlighted the role of teachers as facilitators of reflective learning, 25% emphasized the use of technology and learning analytics, and 15% discussed institutional policies and adaptive curriculum support. The application of the principles of meaningful, mindful, and joyful learning has been proven to create meaningful and sustainable learning experiences. These findings confirm that the synergy between educational policy, pedagogical practices, and technological support is key to strengthening students' basic mathematical foundations. Furthermore, deep learning policies are in line with the 2030 Sustainable Development Goals (SDGs) and the direction of the Merdeka Belajar Curriculum, which is oriented towards 21st-century competencies. Thus, deep learning can be a transformative strategy in building an adaptive, inclusive, and sustainable basic education ecosystem.